The Role of Job Satisfaction in Mediating the Effect of Employe Engagement, Organizational Culture on Employee Performance at Company: Peran Kepuasan Kerja dalam Memediasi Pengaruh Employe Engagement, Budaya Organisasi terhadap Kinerja Karyawan pada Perusahaan - Khasanah, Susinda Umi; Abadiyah, Rifdah (Universitas Muhammadiyah Sidoarjo, 2022)
Human resources will always be needed in every production process either to produce goods or in the field of services, this needs to be considered for companies to always involve employees in the company's development process. the shape and purpose of the organization, various visions are designed to realize human interests which in realizing its mission also involve human resources in it. The purpose of this study was to determine the effect of employee engagement, organizational culture on employee performance through job satisfaction as an intervening variable at PT Sekar Katokichi Sidoarjo. This research is a type of quantitative research that uses data processing in the form of numbers. Using a sample of 141 employees at PT Sekar Katokichi Sidoarjo, with the distribution of questionnaires which were then tested through various measuring instruments using the help of the IBM SPSS program. The results of this study indicate that there is a direct influence of employee engagement on organizational culture on employee performance. Indirect influence of employee engagement, organizational culture on employee performance through job satisfaction as an intervening variable.